2017
DOI: 10.11648/j.sjph.20170506.16
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of El Niño on Diarrheal Disease Incidence: A Systematic Review

Abstract: Climate change is becoming a huge threat to the health especially for those from developing countries. Diarrhea is one of the major diseases linked with changing climate. Global climate change is expected to increase the risk of diarrheal diseases, a leading cause of childhood mortality. El Niño Southern Oscillation (ENSO) is a climate event that originates in the Pacific Ocean but has wide-ranging consequences for weather around the world, and is especially associated with droughts and floods. An El Niño occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In order for health systems to adapt to mitigate the impacts of climate change, evidence is needed of the impacts of extreme weather events on specific outcomes of public health importance. The El Niño-Southern Oscillation (ENSO) phenomenon is a cause of both flooding and droughts across multiple continents and has been shown to be associated with increases in childhood diarrhea in Peru, the United States and elsewhere [43][44][45]. Climate change may increase the frequency of ENSO events as well as the global land area that is subject to its precipitation impacts [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In order for health systems to adapt to mitigate the impacts of climate change, evidence is needed of the impacts of extreme weather events on specific outcomes of public health importance. The El Niño-Southern Oscillation (ENSO) phenomenon is a cause of both flooding and droughts across multiple continents and has been shown to be associated with increases in childhood diarrhea in Peru, the United States and elsewhere [43][44][45]. Climate change may increase the frequency of ENSO events as well as the global land area that is subject to its precipitation impacts [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…While Demisse and Mengisitie [79] noted that El Niño has an impact on diarrhoea incidence for a number of major geographic regions, many of the cited papers address temperature/rainfall-diarrhoea association as opposed to climate driven variations in diarrhoea moderated by ENSO.…”
Section: Diarrhoeamentioning
confidence: 99%
“…Meteorologically, the warmer period of the ENSO is often called El Niño, and the colder period is called La Niña [ 14 ]. Furthermore, ENSO has been proven to impact the morbidity of infectious diseases, such as dengue fever, diarrhea, and malaria [ 15 , 16 , 17 ]. For example, Xiao et al [ 16 ] found that El Niño may have contributed to the dengue fever epidemic from 1995 to 2010 in Guangdong, China.…”
Section: Introductionmentioning
confidence: 99%